1994
DOI: 10.1111/j.1365-2141.1994.tb04852.x
|View full text |Cite
|
Sign up to set email alerts
|

Polycythaemia associated with homozygosity for the abnormal haemoglobin Sherwood Forest (β104 (G6) Arg → Thr)

Abstract: We describe a 22-year-old Pakistani male with polycythaemia associated with homozygosity for a high-affinity haemoglobin mutant, Hb Sherwood Forest. This haemoglobin variant has an amino acid substitution in the beta globin chain at position 104, Arg-->Thr. In the two previously reported instances of this haemoglobin mutant the individuals were heterozygotes and were haematologically normal. We show here that the homozygous state for the mutation is associated with a compensatory erythrocytosis resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…3 According to the x-ray crystallographic study of hemoglobin, the side-chain of Arg(G6) is located on the protein surface of the ␤-subunit, and it does not directly contribute to the heme contact. The mutation at the G6 position, as found in the abnormal hemoglobin, Hb Sherwood Forest, has minor effects on the stability of the globin structure (69), although its oxygen affinity is slightly higher than that of normal hemoglobin (70). In fact, Glu(G6) is also found in other globins such as mammalian myoglobin.…”
Section: Methodsmentioning
confidence: 99%
“…3 According to the x-ray crystallographic study of hemoglobin, the side-chain of Arg(G6) is located on the protein surface of the ␤-subunit, and it does not directly contribute to the heme contact. The mutation at the G6 position, as found in the abnormal hemoglobin, Hb Sherwood Forest, has minor effects on the stability of the globin structure (69), although its oxygen affinity is slightly higher than that of normal hemoglobin (70). In fact, Glu(G6) is also found in other globins such as mammalian myoglobin.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly two decades later, Williamson et al described a young man with polycythemia who was found to be homozygous for the same high-affinity hemoglobin [6]. This was the first reported case of homozygous Hb Sherwood Forest, and it showed that homozygotes had impaired oxygen delivery with a compensatory erythrocytosis.…”
Section: Discussionmentioning
confidence: 99%